Beyond Spectre : confronting new technical and policy challenges ; proceedings of a workshop - Johnson, Anne Frances (Forum on cyber resilience workshop series, 2019)
"In 2017, researchers discovered a vulnerability in microprocessors used in computers and devices all over the world. The vulnerability, named Spectre, combines side effects from caching and speculative execution, which are techniques that have been used for many years to increase the speed at which computers operate. The discovery upends a number of common assumptions about cybersecurity and draws attention to the complexities of the global supply chain and global customer base for the vast range of devices and cloud capabilities that all computer users rely on. In October 2018, the Forum on Cyber Resilience hosted a workshop to explore the implications of this development. This publication summarizes the presentations and discussions from the workshop"--Publisher's description